1992
DOI: 10.3168/jds.s0022-0302(92)77916-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Responses of Lactating Cows to Total Mixed Rations or Computerized Individual Concentrates Feeding

Abstract: A trial was conducted in a commercial dairy herd in which the concentrate part of the ration was fed individually to a group of cows through computerized self-feeders. Performance results were compared with those of a group fed TMR of 65 to 67% concentrates. Rationing of individual concentrates was according to parity, milk yield, milk yield potential, BW changes, and bunk feed-stuffs. Mean intake of concentrates per cow was about 1 kg/d lower in the individually supplemented cows. This was partly compensated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Generally, feeding forages and concentrates as TMR increases DMI when compared to feeding the same ingredients separately (Maltz et al, 1992). In our model, the effect of concentrate feeding is accounted for by the CDMI index, but the feeding technique (TMR v. separate) may contribute to the RMSE difference between the mixed and simple models.…”
Section: Management and Environmental Factors Influencing Intakementioning
confidence: 99%
“…Generally, feeding forages and concentrates as TMR increases DMI when compared to feeding the same ingredients separately (Maltz et al, 1992). In our model, the effect of concentrate feeding is accounted for by the CDMI index, but the feeding technique (TMR v. separate) may contribute to the RMSE difference between the mixed and simple models.…”
Section: Management and Environmental Factors Influencing Intakementioning
confidence: 99%
“…Examples of using on-line recording of real-time parameters as milk yield and live weight as basis for feed management have been presented (Maltz et al, 1991;Maltz et al, 1992). Live weight changes can be used to identify individual cow's energy balance and divide individual lactations in the physiological stages of mobilization and deposition (Maltz et al, 1997) and large variation in duration of the mobilization period of cows offered the same ration are demonstrated (Akinyele and Spahr, 1975;Bossen and Weisbjerg, 2005).…”
Section: Introductionmentioning
confidence: 96%
“…15 (2006): 268-279. ration (TMR) or feeding silage and concentrates separately are both commonly used feeding strategies on dairy farms. In free stall barns, separate concentrate feeding has been accomplished using automatic computerised concentrate feeders (Maltz et al 1992, Yan et al 1998, Yrjänen et al 2003.…”
Section: A G R I C U L T U R a L A N D F O O D S C I E N C Ementioning
confidence: 99%
“…The circumstances might be less optimal for multiparous cows concerning the use of only one TMR in feeding because those cows produce more milk in early lactation and they have a different lactation curve (a clear peak) and energy partitioning compared to primiparous cows. Maltz et al (1992) concluded that computerised dispensing of concentrates can economize on the consumption of concentrates when grouping, and feeding different TMRs is not possible especially in the case of small herds. It is also possible to combine separate concentrate feeding and TMR feeding strategies so that, in addition to TMR, concentrates are fed from automatic feeders.…”
Section: A G R I C U L T U R a L A N D F O O D S C I E N C Ementioning
confidence: 99%
See 1 more Smart Citation